2011
DOI: 10.1038/sc.2011.83
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of depression in survivors of spinal cord injury

Abstract: Study design: Cohort study. Objectives: The objective of this study is to assess depression over a 5-year period in persons with spinal cord injury (SCI) and to assess risk factors for depression over time. Results: In all, 22.1% of participants had PMD at Time 1 and 20.2% at Time 2. There was a nonsignificant trend for change in PMD status (P ¼ 0.058). Of those who had PMD at Time 1, 55.7% had PMD at Time 2. Between the two time points, the most change occurred in the group with clinically significant symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
70
4
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 22 publications
6
70
4
3
Order By: Relevance
“…[1][2][3] This includes the role of negative self-evaluations and coping behaviours in the adjustment process, 4 the impact of chronic neuropathic pain on psychological outcome 4,5 and gender differences in rates of depression post-SCI. 3 Although researchers have made important contributions towards identifying negative outcomes for individuals with SCI using the deficit-based paradigm, 2 it has not assisted researchers in finding ways to prevent psychological problems from developing. 2,6,7 In comparison, the strength-based model of mental health, which evolved from the positive psychology movement, focuses on the variables that buffer against mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This includes the role of negative self-evaluations and coping behaviours in the adjustment process, 4 the impact of chronic neuropathic pain on psychological outcome 4,5 and gender differences in rates of depression post-SCI. 3 Although researchers have made important contributions towards identifying negative outcomes for individuals with SCI using the deficit-based paradigm, 2 it has not assisted researchers in finding ways to prevent psychological problems from developing. 2,6,7 In comparison, the strength-based model of mental health, which evolved from the positive psychology movement, focuses on the variables that buffer against mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed Black and White females with SCI were more likely to have PMD than White males with SCI. 35 The above studies underscore the importance of identifying mediators and implementing statistical controls for other important variables that may be related to depressive symptomatology. Our purpose was to enhance our understanding of depressive symptomatology after SCI related to racial-ethnic differences, while also assessing the relationship of other risk and protective factors for depressive symptoms, including demographic, injury, and socioeconomic variables, health behaviors, and health factors.…”
mentioning
confidence: 99%
“…[5][6][7][8] Depression is the most common type of psychological distress experienced after SCI. 9 Depression in persons with SCI has been associated with a variety of negative health outcomes including reduction in quality of life, less independence in activities of daily living (ADLs), increased frequency of pressure sores and urinary tract infections, greater medical expenses, and higher risk of suicide or requests for terminating life. 7,9,10 It is important to investigate factors that influence an individual's ability to successfully adapt after injury to better understand how to treat and prevent these negative health outcomes.…”
mentioning
confidence: 99%
“…9 Depression in persons with SCI has been associated with a variety of negative health outcomes including reduction in quality of life, less independence in activities of daily living (ADLs), increased frequency of pressure sores and urinary tract infections, greater medical expenses, and higher risk of suicide or requests for terminating life. 7,9,10 It is important to investigate factors that influence an individual's ability to successfully adapt after injury to better understand how to treat and prevent these negative health outcomes. Previous research has identified several variables critical to an individual's ability to respond positively after an SCI, including resilience, social support, and absence of depression.…”
mentioning
confidence: 99%